Modulation of immune-inflammatory responses through surface modifications of biomaterials to promote bone healing and regeneration. (October 2021) - Batool, Fareeha; Özçelik, Hayriye; Stutz, Céline; Gegout, Pierre-Yves; Benkirane-Jessel, Nadia; Petit, Catherine; Huck, Olivier
Control of inflammation is indispensable for optimal oral wound healing and tissue regeneration. Several biomaterials have been used to enhance the regenerative outcomes; however, the biomaterial implantation can ensure an immune-inflammatory response. The interface between the cells and the biomaterial surface plays a critical role in determining the success of soft and hard tissue regeneration. The initial inflammatory response upon biomaterial implantation helps in tissue repair and regeneration, however, persistant inflammation impairs the wound healing response. The cells interact with the biomaterials through extracellular matrix proteins leading to protein adsorption followed by recruitment, attachment, migration, and proliferation of several immune-inflammatory cells. Physical nanotopography of biomaterials, such as surface proteins, roughness, and porosity, is crucial for driving cellular attachment and migration. Similarly, modification of scaffold surface chemistry by adapting hydrophilicity, surface charge, surface coatings, can down-regulate the initiation of pro-inflammatory cascades. Besides, functionalization of scaffold surfaces with active biological molecules can down-regulate pro-inflammatory and pro-resorptive mediators' release as well as actively up-regulate anti-inflammatory markers. This review encompasses various strategies for the optimization of physical, chemical, and biological properties of biomaterial and the underlying mechanisms to modulate the immune-inflammatory response, thereby, promoting the tissue integration and subsequent soft and hard tissue regeneration potential of the administered biomaterial.